Estrategia Educativa Para Cuidadores Informales En Hogares Luz Y Vida Una Institución De Atención A Niños Con Discapacidad. 2021 (2021)
"Disability is a sociocultural and historical construction, which impacts people with disabilities and their caregivers." (1) The objective of developing an educational strategy is to reduce the physical and emotional alterations that informal caregivers of a care home for children with disabilities may suffer and improve the care provided, as well as achieve that the quality of care for children children of the institution is favorable and reduce adverse events due to poor care practices. For this, a research with a quantitative approach was carried out with a quasi-experimental design, with a qualitative technique generated to focus groups and a content analysis. Four modules emerged from the analysis: physical, mental, self-care and biosafety. It was found that the difficulties associated with disability in the areas of the family, society, accessibility, transportation, education system and health coincide with those reported in the literature. Together with this, disability was associated with the social and psychosocial model, perceived mainly as a situation of difference with respect to the conditions in which a person with a disability has. At the same time, the participants show a series of approaches to reduce difficulties and make disability visible. Among these are the active role of people with disabilities, their caregivers, and increasing the responsibility of the State (2). It is concluded that the application of an educational strategy in a group of informal caregivers of a care home for children with disabilities generates a positive effect both on the quality of life of these caregivers and on the quality of care of children with disabilities.